STUDI ELEMEN HINGGA MODEL HIPERBOLIK DAN MODEL ELASTO-PLASTIS HIERARCHICAL SINGLE SURFACE - Hakam, Abdul
Hyperbolic and Hierarchical Single Surface (HiSS) soil models are studied in this research. Hyperbolic model simulates non-linear behavior of soils. HiSS constitutive model, developed by Desai, simulates the non-associative behavior of soils. Both soil models are implemented into non-linear finite element program for analysis and design of soil-structure interaction and geotechnical boundary value problems. Soil model parameters are evaluated from conventional triaxial compression test (CTC). Results of the back-prediction of hyperbolic and HiSS models show that the models can simulate behavior of the soil fairly well in the form of stress-strain and volumetric strain - axial strain responses. The finite element program is verified using the conventional triaxial compression (CTC) test of sand and small scale footing and pile model test. The verification based on CTC tests indicate that the hyperbolic and HiSS soil models have been implemented correctly into finite element program. Program verification on small scale footing model test shows a fairly good agreement between finite element prediction and test results. A good agreement is also obtained for the model pile test. The comparisons of finite element prediction and test result are in the form of load-settlement relationships. The finite element program could be applied as analysis and design method for solving complex soil-structure interaction problems for static loading. The program still need to be improved and further developed to be applied for solving geotechnical problems more widely.